Impact of intravascular ultrasound on Outcomes following PErcutaneous coronary interventioN for In-stent Restenosis (iOPEN-ISR study). (1st October 2021) - Shlofmitz, Evan; Torguson, Rebecca; Zhang, Cheng; Mintz, Gary S.; Dheendsa, Aaphtaab; Khalid, Nauman; Chen, Yuefeng; Musallam, Anees; Rogers, Toby; Hashim, Hayder; Ben-Dor, Itsik; Garcia-Garcia, Hector M.; et al.
Abstract: Background: Percutaneous coronary intervention (PCI) for in-stent restenosis (ISR) remains common. Intravascular imaging allows for the determination of the mechanism of ISR, potentially guiding appropriate therapy. Intravascular ultrasound (IVUS)-guided stent implantation is associated with a reduction in adverse events after PCI, but its impact on treatment of ISR is not clear. Methods: All patients with 1-year follow-up after ISR treatment from 2003 through 2016 were included and stratified by IVUS use. The primary endpoint was the rate of major adverse cardiac events (MACE) at 1 year, defined as the composite of all-cause mortality, Q-wave myocardial infarction, and target vessel revascularization (TVR). Results: The final analysis included 1522 ISR patients, 65.9% of whom were treated with IVUS guidance. The primary endpoint occurred in 18.0% of patients treated with IVUS guidance vs. 24.5% of patients treated with angiography guidance ( p  = 0.0014). Post-dilatation was used more often with IVUS (18.6% vs. 14.1%, p  < 0.001), with a larger diameter of new stents (3.04 ± 0.35 mm vs. 2.94 ± 0.47 mm, p  = 0.001). At 1 year, TVR occurred in 14.5% with IVUS guidance and 19.2% with angiography guidance ( p  = 0.021). Conclusions: The use of IVUS is associated with decreased MACE at 1 year following PCI for ISR. These results support routine IVUS for the treatment of ISR lesions. Highlights: PCI for in-stent restenosis (ISR) remains common. IVUS was associated with significantly fewer MACE at 1 year follow-up in ISR-PCI. A continued benefit was seen at 3-year follow-up. These results support routine IVUS for the treatment of ISR lesions.